Functional genomics in familial dyslipidaemia - Graça, Rafael (2019)
Familial Hypercholesterolemia (FH) is a genetic autosomal dominant disorder characterized clinically by high LDL plasma concentrations from birth causing premature atherosclerosis and coronary heart disease (CHD). The genetic diagnosis is made by finding a functional mutation in one of 3 genes: LDLR (≈90%), APOB (<8%) and PCSK9 (<3%). FH has a frequency between 1/200 and 1/500 for heterozygous and 1/160 000 to 1/1 000 000 for homozygous in most European countries. However, only 40% of the patients enrolled in the Portuguese FH Study carry a putative pathogenic mutation. Other concern point is that less than 15% of the LDLR variants found worldwide in patients with FH diagnosis have functional evidence supporting its pathogenicity.